2008
DOI: 10.1016/j.neuroimage.2007.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal stream development in motion and structure-from-motion perception

Abstract: (2008). Dorsal stream development in motion and structure-from-motion perception. NeuroImage, 39(4): [1815][1816][1817][1818][1819][1820][1821][1822][1823] Little is known about the neural development underlying high order visual perception. For example, in detection of structures by coherently moving dots, motion information must interact with shape-based information to enable object recognition. Tasks involving these different motion-based discriminations are known to activate distinct specialized brain area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
59
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 39 publications
12
59
2
Order By: Relevance
“…-3 -In this study, we used event-related fMRI to examine for the first time the functional development of extrastriate areas involved in BM processing by comparing the activation patterns of 5-to-7-year-old children and adults. Based upon neuroimaging results [14] of dorsal and ventral stream development we hypothesize that for BM processing in children as young as those in our group functional activity within dorsal regions may be substituted for the engagement of networks within the ventral stream, which are known to mature earlier [16]. With accumulated experience and maturation, dorsal regions then become increasingly involved in BM processing.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…-3 -In this study, we used event-related fMRI to examine for the first time the functional development of extrastriate areas involved in BM processing by comparing the activation patterns of 5-to-7-year-old children and adults. Based upon neuroimaging results [14] of dorsal and ventral stream development we hypothesize that for BM processing in children as young as those in our group functional activity within dorsal regions may be substituted for the engagement of networks within the ventral stream, which are known to mature earlier [16]. With accumulated experience and maturation, dorsal regions then become increasingly involved in BM processing.…”
Section: Introductionmentioning
confidence: 78%
“…Following recent studies that have tested the possibility of generalizing results across age for adults and 6 and 7 year old children we transferred the functional and anatomical data of adults and children into a common stereotactic space [14,18]. for the covariates BM, BM_s, SM and SM_s were obtained in each subject while using a temporal high-pass filter (cut-off 128s) and modelling temporal autocorrelation as an AR (1) process.…”
Section: Fmri Acquisition and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In normally developing children, the parsing of the visual array into globally organized forms appears to develop more securely than the equivalent parsing by relative motion (Klaver et al 2008). Numerous reports of elevated global motion thresholds across a variety of neurodevelopmental disorders have prompted researchers to suggest that abnormalities in global motion perception are a result of a general deficiency in the dorsal visual pathway (Pellicano et al 2005).…”
Section: Perturbations Of Normal Maturationmentioning
confidence: 99%
“…Functional brain imaging studies revealed enhanced dorsal visual stream activity in adults compared to children related to motion defined visual perception as well as visuospatial memory and attention Klingberg, 2006;. By contrast object recognition related activity in the ventral stream showed reduced activity related to unspecific object categories (Cantlon et al, 2011;Golarai et al, 2007;Klaver et al, 2008;Lichtensteiger et al, 2008;Passarotti, Smith, DeLano, & Huang, 2007;Peelen et al, 2009). It was suggested that neural tuning may increase neural specificity towards specialized object categories in the ventral stream (Grill-Spector, Golarai, & Gabrieli, 2008), whereas dorsal stream enhancement may reflect consolidation mediated specialization .…”
mentioning
confidence: 99%